Natural agglutinins to African trypanosomes - Ferrante, A.; Allison, A.C. (Wiley, 1983)
Summary Agglutinins to uncoated culture forms of the African trypanosomes, T. congolense and T.b. brucei were detected in sera from a variety of mammals not exposed to the parasites. The agglutinins in bovine serum were shown to be specific antibodies with opsonic properties selective for the species of trypano‐some. These findings suggest a possible role for the glycoprotein coat in preventing access of cross‐reacting antibodies to the plasma membrane of African trypanosomes.